Incidence of Severe Acute Respiratory Syndrome Coronavirus-2 (Sars-Cov-2) Antigen Presence in Adenovirus-Negative Conjunctivitis with Viral Infection Appearance - Fujimoto, Hisataka; Kiryu, Junichi (Journal of Ophthalmology and Research, 2021)
This study aimed to investigate the incidence of the novel coronavirus (SARS-CoV-2) infection (COVID-19) in adenovirus-negative conjunctivitis in Japan. Twelve patients with unilateral or bilateral conjunctivitis with preauricular lymphadenopathy or serous discharge and an initial clinical diagnosis of viral conjunctivitis from April 1, 2020 to September 30, 2020, with negative adenovirus antigen test were included in this study. The residual smeared conjunctiva sample for the adenovirus antigen test was preserved by freezing at –70 °C in a completely anonymized manner. Seven to 180 days after preservation, the samples were tested using the SARS-CoV-2 antigen kit (ESPLINE® SARS-CoV-2 kit, Lot number, K4B00810; FUJIREBIO, Tokyo, Japan). One sample (8.8%) tested positive for the SARS-CoV-2 antigen. None of the patients exhibited systemic symptoms, including pneumonia. No medical staff related to these patients exhibited any infectious findings. These results suggest that the possibility of COVID-19 should be considered with care in daily medical examinations for conjunctivitis, including epidemic keratoconjunctivitis.